Dynamics of classroom motivation: Teacher enthusiasm and the development of math interest and teacher support. (April 2019) - Lazarides, Rebecca; Gaspard, Hanna; Dicke, Anna-Lena
Abstract: Interest is important for successful student learning, but little is known about the developmental dynamics between interest and social support in classrooms. Based on the stage-environment fit theory, this study investigated the interrelation of developmental changes in student class-level interest and perceived teacher support in mathematics classes over one school year after the students transitioned to secondary school. We also examined how teacher-reported enthusiasm was related to these changes. Data of 1000 students (53.6% male) and their classroom teachers ( N = 42), who were surveyed at the beginning of Grades 5 and 6, were analyzed. The results showed a significant decline in class-level mathematics interest and perceived teacher support. Teacher-reported enthusiasm buffered the decline in class-level mathematics interest. When including bidirectional relationships between perceived teacher support and the students' interest, perceived class-level teacher support in Grade 5 positively predicted the change in student interest and, thus, buffered the decline. Highlights: We used multilevel latent change modeling with student and teacher data. Class-level math interest and perceived teacher support declined from Grade 5 to 6. Teacher-reported enthusiasm reduced the decline in students' class-level interest. Student-perceived teacher support reduced the decline in students' class-level interest.